Hydrothermal Activity and Seismicity at Teahitia Seamount: Reactivation of the Society Islands Hotspot? - German, Christopher R.; Resing, Joseph A.; Xu, Guangyu; Yeo, Isobel A.; Walker, Sharon L.; Devey, Colin W.; Moffett, James W.; Cutter, Gregory A.; Hyvernaud, Olivier; Reymond, Dominique (Frontiers in Marine Science, 2020)
Along mid-ocean ridges, submarine venting has been found at all spreading rates and in every ocean basin. By contrast, intraplate hydrothermal activity has only been reported from five locations, worldwide. Here we extend the time series at one of those sites, Teahitia Seamount, which was first shown to be hydrothermally active in 1983 but had not been revisited since 1999. Previously, submersible investigations had led to the discovery of low-temperature (≤30°C) venting associated with the summit of Teahitia Seamount at ≤1500m. In December 2013 we returned to the same site at the culmination of the US GEOTRACES Eastern South Tropical Pacific (GP16) transect and found evidence for ongoing venting in the form of a non-buoyant hydrothermal plume at a depth of 1400m. Multi-beam mapping revealed the same composite volcano morphology described previously for Teahitia including four prominent cones. The plume overlying the summit showed distinct in situ optical backscatter and redox anomalies, coupled with high concentrations of total dissolvable Fe (≤ 186nmol/L) and Mn (≤3nmol/L) that are all diagnostic of venting at the underlying seafloor. Continuous seismic records from 1986-present reveal a ~15 year period of quiesence at Teahitia, following the seismic crisis that first stimulated its submersible-led investigation. Since 2007, however, the frequency of seismicity at Teahitia, coupled with the low magnitude of those events, are suggestive of magmatic reactiviation. Separately, distinct seismicity at the adjacent Rocard seamount has also been attributed to submarine extrusive volcanism in 2011 and in 2013. Theoretical modelling of the hydrothermal plume signals detected suggest a minimum heat flux of 10MW at the summit of Teahitia. Those model simulations can only be sourced from an area of low-temperature venting such as that originally reported from Teahitia if the temperature of the fluids exiting the seabed has increased significantly, from ≤30°C to ~70°C. These model seafloor temperatures and our direct plume observations are both consistent with reports from Loihi Seamount, Hawaii, ~10y following an episode of seafloor volcanism. We hypothesize that the Society Islands hotspot may be undergoing a similar episode of both magmatic and hydrothermal reactivation.